ANALISIS PENGARUH MOTIVASI DAN KEMAMPUAN KERJA TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA ( STUDY PADA PNS SETDA KABUPATEN PATI ) (Students' Journal of Economic and Management, 2013)
This study aimed to determine the effect of motivation on job satisfaction, work ability influence on job satisfaction, motivation influence on the performance, the impact on performance and the ability to work the influence of job satisfaction on the performance of the District Secretariat Pati. The analysis tool used is multiple regression, while the questionnaire is used as a data collector. Measurements using a Likert scale of 7 (seven) alternative answers. The research was conducted at the Office of the Regional Secretariat Pati which has a population of 227 employees. Respondents were obtained through purposive sampling criteria that employees have a minimum education level D3 and obtained total sample of 111 employees. Based on the analysis of this study concluded that: (1) Motivation and significant positive effect on job satisfaction. (2) Ability to work have a positive and significant effect on job satisfaction. (3) Motivation positive and significant effect on the performance. (4) Ability to work has positive and significant impact on the performance. (5) Job satisfaction is a positive and significant effect on the. While mediation tests proved that the variable job satisfaction mediates motivation on performance. Keywords: Motivation, Ability to work, Job satisfaction and Performance.